Partnering with the Devil: The Rationality of the Qur'an on the Use of Charms by Muslim Traders in Selawan Village, Asahan, North Sumatra - Nurdila, Siti; Abbas , Mardhiah (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study explores the practice of using business charm by Muslim traders in Selawan Village, Asahan Regency, as a tradition in the business world that is carried out from generation to generation and has become a cultural heritage among traders. The method used is a case study using primary and secondary data collected through semi-structured interviews. The findings explain that the use of penglaris begins with the reading of verses from the Qur'an accompanied by certain rituals, such as burning kemenyan and incense, as a form of effort to